2016
DOI: 10.4238/gmr.15028370
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and characterization of the or gene in Chinese cabbage (Brassica rapa L. ssp pekinensis)

Abstract: ABSTRACT. Orange inner leaves/heads is a qualitative trait in Chinese cabbage that is controlled by a single recessive gene. Orange head Chinese cabbage contain more carotenoids than its white head counterpart; hence, this trait is of interest to both researchers and consumers. In this study, we selected the orange head Chinese cabbage line 07A163 and the white head Chinese cabbage line Chiifu as test materials. We localized the target gene controlling the orange head trait to the A09 linkage group, with a phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…One gene reported from Chinese cabbage, Bra009770, the homolog of TTG1 on chromosome A06, regulates trichome development and the seed coat color (Zhang et al, 2009). Map-based cloning is one of the most effective ways to isolate genes controlling important agronomic traits (Wei et al, 2013;Ngu et al, 2014;Zou et al, 2016). In our paper, we attempted to clone the gene controlling trichome development in Chinese cabbage using this method.…”
Section: Discussionmentioning
confidence: 99%
“…One gene reported from Chinese cabbage, Bra009770, the homolog of TTG1 on chromosome A06, regulates trichome development and the seed coat color (Zhang et al, 2009). Map-based cloning is one of the most effective ways to isolate genes controlling important agronomic traits (Wei et al, 2013;Ngu et al, 2014;Zou et al, 2016). In our paper, we attempted to clone the gene controlling trichome development in Chinese cabbage using this method.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the PCR was cooled down and kept at 4 °C. The OR mutant, responsible for orange color, was confirmed by using the OR mutant-specific primers [41].…”
Section: Methodsmentioning
confidence: 99%
“…The Or gene is known to cause weakly pigmented or unpigmented tissues to turn orange in cauliflower (Li et al 2001), and the Br-Or gene was mapped and shown to confer orange inner leaf color in Chinese cabbage (Feng et al 2012). Molecular markers derived from Br-or and BrCRISTO1 cause orange-colored inner leaves in Brassica rapa (Zhang et al 2013;Lee et al 2014;Zou et al 2016), and loss of BrCRISTO1 function confers orange color to the inner leaves of Chinese cabbage (Su et al 2015;Zhang et al 2015). In addition, BrPur and BrMYB2 have been mapped and shown to be tightly linked to the purple-leaf phenotype (Wang et al 2014;He et al 2020).…”
Section: Leaf Color Mutants Are Valuable Genetic Resources For Chinese Cabbage Breedingmentioning
confidence: 99%